Evaluation of polymeric membranes' performance during laboratory-scale experiments, regarding the CO2 separation from CH4. (July 2022) - Koutsiantzi, Chrysovalantou; Mitrakas, Manassis; Zouboulis, Anastasios; Kellartzis, Ioannis; Stavropoulos, George; Kikkinides, Eustathios S.
Abstract: The present study evaluates the separation performance of a commercially available polymeric membrane, when employed for the upgrade of biogas to enrich CH4 from a simulated binary gas mixture. For this purpose, a laboratory-scale membrane set-up device has been designed and assembled, aiming to achieve the production of high purity biomethane (>95%) with simultaneous recycling and utilization of the (considered as) waste CO2 stream. The examined membrane is a polysulfone (PSF) hollow fiber (HF) one, applied in counter-current flow. The feed concentration of gases consisted between 55-70 vol% and 45–30 vol%, regarding CH4 and CO2 respectively, whereas the effect of retentate pressure was studied in the range between 0.7 and 1.5 bars. The experimental results reveal that the concentration of CH4 in the retentate stream can exceed the target value of 95%, when the applied pressure values are above the limit of 1 bar. Any increase in the feed pressure can lead also to higher CH4 purity on the retentate side, however the retentate mass flow decreases, leading to smaller recovery values of CH4 . A significant increase in the CH4 purity is observed, when the CH4 recovery drops below 40%, suggesting the need for the application of multiple membrane modules, operating in series. Regarding the CO2 concentration in the permeate stream, its percentages range between 30 and 50%, which are not considered as sufficient to permit immediate reuse, whereas the need of extra membrane modules to improve the purity of gas streams is confirmed. Graphical abstract: Image 1 Highlights: 1-stage laboratory pilot scale device was assembled for the separation of CO2 from CH4, simulating the major biogas components. A polysulfone (PSF) hollow fiber membrane module was evaluated for the CH4 –CO2 separation in continuous flow. The major process parameters examined, affecting the performance of separation for the initial gas mixture. Gas separation is achieved at low pressures, while methane purity exceeds 95% at 1 bar and higher. Feed flow ranges between 1000 and 3000 mL/min for every laboratory test.